Alevi cultural heritage in Turkey and Germany: negotiating “useable pasts” in transnational space - Weineck, Benjamin (European journal of Turkish studies, 2015)
The accelerating references to Cultural Heritage in politics and scholarship have impacted on ‘vernacular’ or migrant communities’ aspirations for the recognition of their distinct identities and have likewise influenced nation-states’ policies on cultural diversity. Thus Alevi communities in Turkey and Germany have used the institutions and language provided by intergovernmental actors to claim recognition of their Intangible Cultural Heritage. In 2010, the Alevi-Bektaşi ritual dance, semah, was inscribed onto Turkey’s National Inventory for Intangible Cultural Heritage. However, Alevis in Germany, also drawing on the semah as their “useable past”, recently initiated their own heritage project. This paper analyses the various functions and uses of heritage discourse in the context of its exercise by both state and non-state actors in Germany and Turkey. It will be argued that a critical investigation must question the empowering and disciplining aspects of the governmentalities of Cultural Heritage because, as demonstrated by the Turkish case, recognition of (Alevi) heritage does not necessarily translate into legal recognition.